The Knowledge of Traditional Constructiv Systems and its Contribution for a Sustainable Practice in Architecture. The Example of the Bougeois House of Porto - Rui Póvoas (2014)
This paper intends to present a constructive model of the bourgeois house of Porto, conceived from the evidences of systematization that appeared along the research on materials and techniques applied in its construction, aiming, fundamentally, its application in the development of intervention projects in these buildings. Moreover, it is expected that all the work of characterization and typification related with the conception of this constructive model, may also constitute an important contribution for the History of Construction in Portugal.